2018
DOI: 10.24326/asphc.2018.6.2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PRUNE Prunus domestica CONSUMPTION ON BLOOD LIPID PROFILE IN PATIENTS WITH MODERATE HYPERCHOLESTEROLEMIA

Abstract: Most of chemical and nutritional plum properties presented in the literature relate to cultivars grown in warm climates. The aim of the study was to assess the effect of prune consumption on blood lipid profiles in patients with moderate hypercholesterolemia. It used plums originating from temperate climates, characterized by lower sugar and higher polyphenol content than fruits grown in areas with greater sunlight. The study was conducted using Prunus domestica cv. 'Valor' plums, dried using the pulsed fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In line with our findings, a previous study found that eating 100 g of prunes daily for 6 weeks reduced LDL‐C and TC levels in patients with moderate hypercholesterolemia. In addition, there were no notable alterations in the levels of HDL or TG; this study lacked a control group (Walkowiak‐Tomczak et al., 2018 ). Similarly, According to a cross‐over design study by Tinker et al., men with mild hypercholesterolemia who consumed 12 prunes per day for 8 weeks saw an increase in fiber intake and a decrease in LDL and total cholesterol levels.…”
Section: Discussionmentioning
confidence: 87%
“…In line with our findings, a previous study found that eating 100 g of prunes daily for 6 weeks reduced LDL‐C and TC levels in patients with moderate hypercholesterolemia. In addition, there were no notable alterations in the levels of HDL or TG; this study lacked a control group (Walkowiak‐Tomczak et al., 2018 ). Similarly, According to a cross‐over design study by Tinker et al., men with mild hypercholesterolemia who consumed 12 prunes per day for 8 weeks saw an increase in fiber intake and a decrease in LDL and total cholesterol levels.…”
Section: Discussionmentioning
confidence: 87%